Cortex Moutan Induces Bladder Cancer Cell Death via Apoptosis and Retards Tumor Growth in Mouse Bladders. (24th October 2013) - Lin, Mei-Yi; Lee, Ying-Ray; Chiang, Su-Yin; Li, Yi-Zhen; Chen, Yueh-Sheng; Hsu, Cheng-Da; Liu, Yi-Wen
Abstract : Cortex Moutan is the root bark of Paeonia suffruticosa Andr. It is the herbal medicine widely used in Traditional Chinese Medicine for the treatment of blood-heat and blood-stasis syndrome. Furthermore, it has been reported that Cortex Moutan has anticancer effect. In this study, the Cortex Moutan extract was evaluated in bladder cancer therapy in vitro and in vivo. Cortex Moutan extract reduces cell viability with IC50 between 1 2 mg/ml in bladder cancer cells, and it has lower cytotoxicity in normal urotheliums. It arrests cells in G1 and S phase and causes phosphatidylserine expression in the outside of cell membrane. It induces caspase-8 and caspase-3 activation and poly(ADP-ribose) polymerase degradation. The pan caspase inhibitor z-VAD-fmk reverses Cortex Moutan-induced cell death. Cortex Moutan also inhibits cell invasion activity in 5637 cells. In mouse orthotopic bladder cancer model, intravesical application of Cortex Moutan decreases the bladder tumor size without altering the blood biochemical parameters. In summary, these results demonstrate the antiproliferation and anti-invasion properties of Cortex Moutan in bladder cancer cells and its antibladder tumor effect in vivo. Cortex Moutan may provide an alternative therapeutic strategy for the intravesical therapy of superficial bladder cancer.